Extensiveness of Internal School Quality Assurance Feedback in Enhancing Learners’ Achievement in Public Primary Schools in Rombo District, Tanzania - Assenga, Paul; M, Muteti Catherine; Mbua, Fortunatus M. (International Journal of Scientific Research and Management (IJSRM), 2024)
Improving learner achievement and school quality in general, depends on offering top-notch instruction. Capitalizing on public primary schools in Rombo district, Tanzania, the study investigated the extent of Internal School Quality Assurance Feedback (ISQAF) on learner success in education. Anchored in total quality management philosophy, the study employed convergent design under the mixed-methods approach. From the target population of 1,127 individuals and 151 primary schools, the study sampled 124 individuals from 16 primary schools, and one District School Quality Assurer using simple random, total population, stratified random, and expert sampling techniques. Research experts in educational planning and administration at MWECAU validated the data collection instruments. The Cronbach's Alpha technique based on the Likert-type item of the pilot-tested instruments was used to establish the reliability of questionnaires for teachers and  ISQAs, and the coefficients of  0.762 and 0.816 were consecutively achieved. The trustworthiness of the qualitative data was achieved through peer debriefing and triangulation methods. Quantitative data was descriptively analyzed to frequencies, percentages, and means and presented in a table using SPSS software version 22 while thematic analysis was applied to the qualitative data. According to the research, ISQAF raises pupil achievement by encouraging academic development, enhancing instruction, developing problem-solving techniques, creating supportive learning environments, and promoting creativity. The study concludes that ISQAF is timely and has essentially improved learner performance in public primary schools in  Rombo district. To help teachers become even more proficient with ISQAF, the study suggested government funding programs for ongoing professional development.